Hymenolepis diminuta (Rodolphi, 1819) Infection in a Child from Iran - Gh Mowlavi; I Mobedi; S Mamishi; M Rezaeian; MT Haghi Ashtiani; M Kashi (Tehran University of Medical Sciences, 2008)
Hymenolepis diminuta is a cestode frequently found in rodents and humans. Species of flour moths of the genus Pyralis and beetles in the genus Tribolium are common intermediate hosts. Humans can be accidentally infected through the ingestion of the insects, including larvae in precooked cereals, dried fruits or other food items, and directly by ingesting the insects from the environment. This tapeworm, while infrequently encountered, has been reported from many parts of the world. In this paper we report the first case of infection with H.diminuta in Iran since 1972.